Strategi Guru dalam Mengatasi Rendahnya Minat Siswa terhadap Pembelajaran IPS di SD - Erni Erni; Muhammad Kaulan Karima; Bella Dwi Arditha; Faiz Kurniawan; Gita Adella; Loudhea Anggraeni; Tisya Aulia Anggraeni; Vinsensia Lugita Ines; Fildzah Aulia Putri (Politeknik Kampar, 2025)
Social Studies (IPS) is an important subject in shaping the character and national insight of students from an early age. However, the reality shows that many students at the elementary school level have low interest in learning IPS. This study aims to explore the strategies implemented by teachers in overcoming low student interest in learning IPS, as well as the effectiveness of these strategies in increasing motivation and learning participation. The study used a qualitative approach with interview methods, observations, and documentation studies conducted on two fifth grade teachers at SD Negeri 1 Metro Pusat, Lampung. The results showed that students' interest in IPS was influenced by learning methods, media used, internal motivation, student character, and the role of parents. The strategies implemented by teachers included the use of visual and audio media, contextual learning, role play, giving awards, and a personal approach to understanding students' backgrounds. Teachers also tried to explore students' non-academic potential through extracurricular activities. Although these strategies are not always effective for all students, an adaptive and sustainable approach has been shown to increase students' participation and enthusiasm for learning in general. This study concludes that the success of social studies learning is highly dependent on the creativity of teachers in creating an interesting learning atmosphere, support from the family environment, and the active involvement of the school in providing facilities and learning support programs.